Comparing Four Video Laryngoscopes and One Optical Laryngoscope with a Standard Macintosh Blade in a Simulated Trapped Car Accident Victim. (1st October 2019) - Raimann, Florian J.; Tepperis, Daniel M.; Meininger, Dirk; Zacharowski, Kai; Schalk, Richard; Byhahn, Christian; Weber, Christian F.; Mutlak, Haitham
Abstract : Background . Tracheal intubation still represents the "gold standard" in securing the airway of unconscious patients in the prehospital setting. Especially in cases of restricted access to the patient, video laryngoscopy became more and more relevant. Objectives . The aim of the study was to evaluate the performance and intubation success of four different video laryngoscopes, one optical laryngoscope, and a Macintosh blade while intubating from two different positions in a mannequin trial with difficult access to the patient. Methods . A mannequin with a cervical collar was placed on the driver's seat. Intubation was performed with six different laryngoscopes either through the driver's window or from the backseat. Success, C/L score, time to best view (TTBV), time to intubation (TTI), and number of attempts were measured. All participants were asked to rate their favored device. Results . Forty-two physicians participated. 100% of all intubations performed from the backseat were successful. Intubation success through the driver's window was less successful. Only with the Airtraq® optical laryngoscope, 100% success was achieved. Best visualization (window C/L 2a; backseat C/L 2a) and shortest TTBV (window 4.7 s; backseat 4.1 s) were obtained when using the D-Blade video laryngoscope, but this was not associated with a higher success through the driver's window. Fastest TTI was achieved through the window (14.2 s) when using the C-MAC video laryngoscope and from the backseat (7.3 s) when using a Macintosh blade. Conclusions . Video laryngoscopy revealed better results in visualization but was not associated with a higher success. Success depended on the approach and familiarity with the device. We believe that video laryngoscopy is suitable for securing airways in trapped accident victims. The decision for an optimal device is complicated and should be based upon experience and regular training with the device.